Estimasi Jarak Tempuh Order Picking Manual Dengan Metode Analitik di PT. GMS - Chandra, Agung (Department Industrial Engineering, University of Muhammadiyah Malang, 2014)
Travel distance has a significant role in warehousing productivity. One way to calculate travel distance is to use analytical method, in term of average travel distance. Routing strategy implemented, S-shape / traversal strategy and Return strategy, random storage method are used in this paper at PT.GMS. The components of average travel distance are used to calculate: traveling distance from the depot to the first pick aisle, traveling distance through subaisle with picks, correction of travel distance for turns within subaisle, traveling distance in the cross aisle while picking, traveling distance back to the depot if all picks in one block, and total average travel distance. The results show the total average travel distance using S-shape is 41.4095 meter and return strategy is 45.7165 meter.